Determination of trace elements (Cr, AI, Pb) by atomic absorption in natural water of Kyiv - Polumbryk, Maksim; Ishchenko, Vera; Polumbryk, Oleg (My University, 2014)
The control of microelements in water is a one of the most important factor of the humans health in urbanized cities. ETAAS method with chemical modifiers has been used in drinking water analysis.
Keywords: ETAAS; microelement; water; nature; drinking; вода; микроэлемент; природа; пити; мікроелементів; кафедра екології та екоменеджменту; кафедра харчової хімії